Peran Media Sosial Facebook sebagai Media Informasi Pemilihan Kepala Daerah - Andion Sefda Mulyawan; Eceh Trisna Ayuh (JOPPAS: Journal of Public Policy and Administration Silampari, 2026)
This study aims to analyze the role of Facebook as an information medium for first-time voters in the 2024 Bengkulu Tengah regional election. This research uses a qualitative approach with a case study method through in-depth interviews and observation of social media activities. The results show that Facebook plays an important role in shaping public, media, and policy agendas. The main issues highlighted include employment, infrastructure, education, and internet access. Facebook also serves as an effective platform for delivering candidates’ visions and missions in an engaging and accessible manner for young voters. In conclusion, Facebook has a strategic role in shaping perceptions, increasing political engagement, and influencing the decisions of first-time voters in regional elections. Keywords: Agenda Setting, Facebook, New Voters, Regional Elections, Social Media.